Occurrence of tornado outbreaks influenced by solar wind–magnetosphere–ionosphere–atmosphere coupling - Prikryl, Paul; Rušin, Vojto (Advances in science and research, 2025)
The occurrence of tornado outbreaks in the United States is investigated in the context of solar wind coupling to the magnetosphere-ionosphere-atmosphere system. The superposed epoch analysis of daily occurrence of tornadoes reveals a peak in the cumulative number of tornadoes near the interplanetary magnetic field sector boundary crossings. Most of the large tornado outbreaks are associated with high-density plasma adjacent to the heliospheric current sheet and with co-rotating interaction regions at the leading edge of high-speed streams. Large tornado outbreaks also followed impacts of interplanetary coronal mass ejections or occurred in the declining phase of major high-speed streams. We consider the role of aurorally generated atmospheric gravity waves in severe weather development leading to tornado outbreaks. While these gravity waves reach the troposphere with attenuated amplitudes, they can contribute to conditional symmetric instability release in frontal zones of extratropical cyclones leading to synoptic-scale weather conditions favouring formation of supercells in a strong wind shear environment and high tornado occurrence.